Generation of quadrature squeezed light by cross-phase modulation in semiconductors - von Plessen, G; Fox, A; Dabbicco, M; Schucan, G; Ryan, J (1996)
A technique in which quadrature squeezing can be achieved in a semiconductor crystal using a linearly polarized pump pulse to generate orthogonally polarized squeezed light is presented. This technique is unique to crystalline materials and should be particularly useful for the generation of squeezed light in semiconductor waveguides. The method makes use of the properties of the third-order nonlinear susceptibility at photon energies slightly below half the band gap, and generates the squeezed light by four-wave mixing in traveling-wave geometry. The squeezed light is produced by cross-phase modulation and is orthogonally polarized to the pump.